The arisal of data spaces: why I am excited and worried - Peeters, Liesbet M. (Frontiers in Immunology, 2024)
is an assistant professor, leading the research group of biomedical data sciences at Hasselt University (Belgium). This research group is affiliated to both the Biomedical Research Institute as well as the Data Science Institute. They are a multidisciplinary team that consist of researchers with a (bio)medical background as well as with a data science background (and everything in between). Together, they make the connections between the two very different worlds of biomedical sciences and data sciences. Their research focuses on investigating how the use of innovative technologies to handle and analyze real-world data can transform our health and care system as well as how to overcome the socio-technical challenges that arise with scaling-up realworld data. Until now, research outputs have focused mainly on multiple sclerosis (MS), but more recently other clinical domains such as cardiovascular disorders, diabetes, risk pregnancies are being explored. Liesbet is the founder and chair of multiple initiatives like the MS Data Alliance, OHDSI Belgium and the MS DataConnect initiative within the University MS Center. Her team is an active contributor within the ELIXIR Belgium consortium, the OHDSI community and she is currently acting as the head of EBRAINS Belgium.